1964
DOI: 10.1302/0301-620x.46b2.314
|View full text |Cite
|
Sign up to set email alerts
|

Tears of the Humeral Rotator Cuff

Abstract: 1. Radiographs of both shoulders were performed on 106 unselected necropsy subjects and those found to be abnormal were examined pathologically. 2. Radiological abnormalities were found in sixty-eight shoulders of thirty-eight subjects. Pathological examination showed rotator cuff tears and associated abnormalities in thirty-five of these, rheumatoid arthritis in one, a previous fracture in one, and one was not examined. 3. The criteria for radiological diagnosis of rotator cuff tears are examined and discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

1981
1981
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(25 citation statements)
references
References 0 publications
2
21
0
2
Order By: Relevance
“…DFV cannot capture of all the kinematic factors involved in defining AHI, but it does allow for dynamic analysis using methods of radiographic image acquisition and measurement frequently used to diagnose rotator cuff injury. 10,15,45 Although our AHI findings were similar to previous MRI studies with muscle activity, 17,18,22 limitations due to 2-dimensional viewing and lack of ability to visualize soft tissue structures, such as articular cartilage and the supraspinatus tendon, do exist in this method of AHI analysis. Despite the limitations, the use of DFV adds an important dynamic component to the understanding of subacromial space changes during arm elevation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…DFV cannot capture of all the kinematic factors involved in defining AHI, but it does allow for dynamic analysis using methods of radiographic image acquisition and measurement frequently used to diagnose rotator cuff injury. 10,15,45 Although our AHI findings were similar to previous MRI studies with muscle activity, 17,18,22 limitations due to 2-dimensional viewing and lack of ability to visualize soft tissue structures, such as articular cartilage and the supraspinatus tendon, do exist in this method of AHI analysis. Despite the limitations, the use of DFV adds an important dynamic component to the understanding of subacromial space changes during arm elevation.…”
Section: Discussionsupporting
confidence: 79%
“…10,11,[15][16][17][18][19]21,45 Narrowing of the AHI has been observed during arm elevation in healthy individuals, 11,19,21 with even greater narrowing observed during muscle activity in individuals with SIS. 18 Scapular retraction 48 and adduction muscle activity 19 have both been shown to widen the space, and Desmueles et al 11 reported a strong positive relationship between the reduction of AHI narrowing and functional improvement in SIS patients.…”
mentioning
confidence: 99%
“…Previous authors have already described radiographic signs of RC tears. [14][15][16] None of the patients in our study had these findings. Kivimäki and Ahoniemi 2 found a mean ACJ space of 3.7 mm in SCI patients and 4 mm in able-bodied, which is similar to our work.…”
Section: Discussionmentioning
confidence: 90%
“…Generally, a healthy range has been found to be between 6 and 7 and 13 and 14 mm, and an unhealthy range below 4 to 5 mm. 9,16,39 Thus, a transitional area with inconsistent injury states appears to exist between 4 and 7 mm. With this large grey area, coupled with excursion measurements taken on such a small scale, a persistent discrepancy exists regarding the significance of humeral head excursion.…”
Section: Statistical Vs Clinical Significance Of Excursionmentioning
confidence: 99%